Patterns and Characteristics of Uterine Fibroids among Women Attending a Tertiary Maternity Hospital in Sana'a City, Yemen - Hanan M. Hasan; Amal A. Mohammed; Maha Abdulaziz (University of Science and Technology, Sana’a, Yemen, 2025)
Background: Uterine fibroids are the most common benign pelvic tumors in women of reproductive age and a major cause of gynecologic morbidity. While global and regional prevalence data exist, no published studies have described their patterns and characteristics in Yemen. Therefore, this study aimed to describe the demographic, reproductive, and clinical features of uterine fibroids among women attending a tertiary maternity hospital in Sana’a City, Yemen. Methods: A descriptive cross-sectional study was conducted using retrospective data from January 1 to December 31, 2022, at Al-Sabeen Maternity Hospital in Sana’a. Medical records of 171 women diagnosed with uterine fibroids who underwent hysterectomy or myomectomy were reviewed. Data on demographic factors, reproductive history, fibroid characteristics, and surgical management were extracted and analyzed. Results: Of the 171 women with uterine fibroids, most were aged >40 years (45%), followed by 30–40 years (35.7%), with 19.3% younger than 30 years. Menarche under the age of 12 years was reported by 52.6% of women, and most were multiparous (64.3%). A positive family history was uncommon (2.3%). More than half of women (54.4%) had a single fibroid, while 45.6% had multiple fibroids. Intramural fibroids predominated (81.3%), followed by subserosal (21.1%) and submucosal (17.5%) types, with broad ligament (4.7%) and cervical (1.8%) sites being rarely affected. Myomectomy was performed in 62.6% of cases and hysterectomy in 37.4%. Multiple and submucosal fibroids were more frequent in women with early menarche, whereas single and intramural fibroids were more common in those with later menarche. Multiple fibroids were more common in nulliparous women, whereas single fibroids predominated among multiparous women. Conclusion: Uterine fibroids are most frequently found in women over 40 years of age, suggesting a potential association between advancing age and fibroid development. Early menarche and nulliparity are more commonly linked to multiple fibroids, particularly subserosal and submucosal types, whereas multiparous women more often present with single and intramural fibroids. These patterns indicate that both age at menarche and reproductive history may influence fibroid number and anatomical location. Recognizing these trends can enhance clinical assessment and guide more tailored, patient-centered management strategies.